The impact of frailty on quality of life among older adults in nursing homes: the mediating role of psychological resilience - Zhang, Jiquan; Qing, Wei; Zhou, Yang; Zhou, Jingru; Xu, Fan (Frontiers in Public Health, 2025)
BackgroundAs China’s population ages, nursing homes are becoming increasingly important in the care system for older adults. However, older adults in nursing homes often face high health risks and challenges to their quality of life (QOL) due to advanced age, disability, and multiple coexisting illnesses. Frailty, as a multidimensional clinical syndrome associated with age, significantly affects the QOL of older adults.ObjectiveTo investigate the mediating role of psychological resilience in the relationship between frailty and QOL among older adults in nursing homes.MethodsA cross-sectional survey method was employed, with 302 older adults residing in nursing homes in China from August to November 2022 selected as the study subjects. A questionnaire survey was conducted using a general information questionnaire, the Tilburg Frailty Indicator (TFI), the Connor-Davidson Resilience Scale (CD-RISC 25), and the Medical Outcomes Study 36-Item Short Form Health Survey (SF-36). Data analysis was performed using SPSS 26.0 and its PROCESS macro program.ResultsFrailty among older adults in nursing homes significantly negatively predicted QOL (β = −0.224, p < 0.001), and psychological resilience partially mediated the relationship between frailty and QOL, accounting for 41.55% of the total effect. Frailty indirectly affected QOL by reducing psychological resilience (β = 0.093, 95% CI = [−0.150, −0.050]).ConclusionPsychological resilience is a key mediating variable between frailty and QOL. Enhancing the psychological resilience of older adults in nursing homes can help mitigate the negative impact of frailty on QOL, providing a theoretical basis and practical guidance for improving the QOL of older adults in nursing homes.